Protestantisme med kød og blod - Gregersen, Niels Henrik (Dansk Teologisk Tidsskrift, 2010)
In this article, “Protestantism with blood and flesh”, it is argued that a Lutheran theology cannot and should not be reduced to general Protestant principles. Luther’s theology emerged as a result of renewed attentiveness to the basic expressions of the gospel: the audible word of God, the visible sacraments, the bodily aspects of communal life, and the evangelical signs of creation. The so-called Protestant Principles, at their best, are to be regarded as second-order and summarizing expressions of the primary life-utterances of the church, and of the corresponding experiences in ordinary life. Moreover, at a closer inspection the exclusive particles such as solo Christo and sola fide are to be taken as inclusive particles that provide a participation in God, enacted in faith, hope and love.